Multiple Encounters: Queer Migrants and Bureaucratic Violence - Lins França, Isadora; Nzinga Ribeiro, Bruno (Refuge, 2023)
In this paper, we analyze the multiple encounters queer asylum seekers face due to violence embedded in border control and asylum recognition processes. This analysis is based on the reconstitution of two narratives that form part of an ethnographic study, the result of five years of fieldwork with queer migrants in Brazil and Spain. We employ the notion of bureaucratic violence to understand the ambiguities between control and protection in the emergence of the LGBTI refugee as a subject of rights in the humanitarian realm.